Peripheral intravenous catheter and intraosseous device insertions reported from the 1st July 2016 to 30th June 2017 in an Australian state ambulance service: An observational study. (December 2022) - Mason, Matt; Wallis, Marianne; Barr, Nigel; Matagian, Nicholas; Lord, Bill
Abstract: Objective: To overcome the lack of larger, population-based studies reporting the prevalence of insertion of PIVCs and IO devices, and to describe the patient-related and service-related characteristics of these devices, inserted by paramedics, in an Australian state ambulance service. Methods: A retrospective analysis of the electronic Ambulance Report Form (medical record) and Computer Aided Dispatch system from the 1st July 2016 until 30th June 2017. Results: 709, 217 events were analysed. Of these, 20.4% involved at least one successful PIVC insertion and 0.07% involved at least one successful IO device insertion; most of the time on first attempt (89% and 86.4% respectively). Most PIVCs were inserted into the right antecubital fossa or dorsum of the right hand while IO devices were inserted into the proximal tibia. Of male patients, 21.4% received PIVCs while 19.5% of female patients received PIVCs. Very low numbers of both male and female patients received IOs (0.1%). Medical, non-traumatic presentations were the most common presentation and received the most insertions of both devices, followed by trauma presentations. Advanced Care Paramedics inserted 84.0% of PIVCs while Critical Care Paramedics inserted 94.4% of IO devices. Time treating and transporting patients generally increased with number of attempts at vascular access undertaken. Conclusions: Queensland paramedic practices relating to insertion of PIVCs, and IO devices appears consistent with documented practice internationally. Further study is required to determine whether the antecubital fossa and dorsum of the hand insertions are clinically necessary in this population as areas of flexion and distal extremities are generally to be avoided for PIVC insertion.